Analysis of prosthetic risk factors for peri-implant medication-related osteonecrosis of the jaw: an observational study - Da Young Kim; Sunyoung Choi; Jeong Joon Han (Scientific Reports)
Abstract The study aimed to evaluate clinical characteristics of peri-implant medication-related osteonecrosis of the jaw (PI-MRONJ) and to identify prosthetic risk factors for PI-MRONJ. Demographic and pharmacological data were collected from 32 patients. Radiographic assessments were performed to evaluate potential risk factors related to prosthetic elements, including prosthesis margin, embrasure space, emergence profile and angle, span of prostheses, and cantilever extensions. 24 patients were classified as having implant presence-triggered PI-MRONJ, while 8 were categorized as having implant surgery-triggered PI-MRONJ. Even in well-functioning implants, MRONJ developed after an average of 48.3 months following the initiation of anti-resorptive drug (ARD) therapy. Similarly, in implants placed during ARD therapy and showing successful osseointegration, MRONJ occurred after an average of 23.3 months of implant placement. Comparing prostheses in MRONJ-affected areas to those in unaffected areas, the presence of cantilever extensions showed the only significant difference (p = 0.002). Regression analysis revealed that cantilever extensions (p = 0.001), sex (p = 0.009), duration of ARD (p = 0.042), and age (p = 0.046) were significantly associated with PI-MRONJ. These findings suggest that non-axial loading may be a risk factor for PI-MRONJ. Proper prosthetic design and load management, along with long-term monitoring, are crucial for preventing PI-MRONJ.